Endoscopic treatment of biliary stenosis in patients with alveolar echinococcosis: report of 7 consecutive patients with serial ERC approach - Stojković, Marija; Junghanss, Thomas; Veeser, Mira; Weber, Tim; Sauer, Peter (PLoS neglected tropical diseases, 2016)
Background and Aims Biliary vessel pathology due to alveolar echicococcosis (AE) results in variable combinations of stenosis, necrosis and inflammation. Modern management strategies for patients with cholestasis are desperately needed. The aim is proof of principle of serial ERC (endoscopic retrograde cholangiography) balloon dilation for AE biliary pathology. Methods Retrospective case series of seven consecutive patients with AE-associated biliary pathology and ERC treatment in an interdisciplinary endoscopy unit at a University Hospital which hosts a national echinococcosis treatment center. The AE patient cohort consists of 106 patients with AE of the liver of which 13 presented with cholestasis. 6/13 received bilio-digestive anastomosis and 7/13 patients were treated by ERC and are reported here. Biliary stricture balloon dilation was performed with 18-Fr balloons at the initial and with 24-Fr balloons at subsequent interventions. If indicated 10 Fr plastic stents were placed. Results Six patients were treated by repeated balloon dilation and stenting, one by stenting only. After an acute phase of 6 months with repeated balloon dilation, three patients showed “sustained clinical success” and four patients “assisted therapeutic success,” of which one has not yet reached the six month endpoint. In one patient, sustained success could not be achieved despite repeated insertion of plastic stents and balloon dilation, but with temporary insertion of a fully covered self-expanding metal stent (FCSEMS). There was no loss to follow up. No major complications were observed. Conclusions Serial endoscopic dilation is a standard tool in the treatment of benign biliary strictures. Serial endoscopic intervention with balloon dilation combined with benzimidazole treatment can re-establish and maintain biliary duct patency in AE associated pathology and probably contributes to avoid or postpone bilio-digestive anastomosis. This approach is in accordance with current ERC guidelines and is minimally disruptive for patients.
Gesehen am 15.05.2020